Do buyer groups facilitate collusion? - Hans-Theo Normann; Jürgen Rösch; Luis Manuel Schultz (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2014)
We explore whether lawful cooperation in buyer groups facilitates collusion in the product market. Buyer groups purchase inputs more economically. In a repeated game, abandoning the buyer group altogether or excluding single firms constitute credible threats. Hence, in theory, buyer groups facilitate collusion. We run several experimental treatments using three-firm Cournot markets to test these predictions and other effects like how buyer groups affect outcomes when group members can communicate. The experimental results show that buyer groups lead to lower outputs when groups can exclude single firms. Communication is often abused for explicit agreements and this strongly reduces competition.
Keywords: C7; C9; L4; L41; 330; buyer groups; cartels; collusion; communication; experiments; repeated games